Management of the pregnant trauma patient: A literature study - Louise D' Argent; Sandra Verelst; Marc Sabbe (Open Journal of Trauma - Peertechz Publications, 2020)
Background: Trauma frequently occurs during pregnancy and can affect both mother and unborn child. It is essential to consider pregnancy in every female trauma patient of reproductive age. The management of a pregnant trauma patient is often considered to be complicated. Main body: Therefore, it is important to follow a clear management protocol of the appropriate approach of the pregnant trauma patient. Furthermore, some pregnancy-specific complications of trauma such as placental abruption, uterine rupture, premature uterine contractions and their management are presented. In pregnancy, the ABCDEF approach is used during the primary survey with the 'F' standing for fetus. Fetal vital signs are an important indicator of the maternal condition, and fetal outcome depends on maternal wellbeing. Concerning the secondary survey, a physical examination as well as indicated technical examinations should be performed with fetal monitoring being essential in a viable pregnancy. In case of non-reassuring findings, emergency caesarean section or laparotomy may be indicated. In case of cardiac arrest, advanced trauma life support management should be started and the aetiology of cardiac arrest should be sought using the BEAUCHOPS tool. Early airway protection with adequate oxygenation and ventilation as well as effective chest compressions with tilting of the mother or manual displacement of the uterus, are essential.  Conclusion: A systematic approach (ABCDEF) of the traumatised pregnant patient is even more essential than in the non-pregnant patient. Saving the mother is crucial if you also want to save the unborn child.